MANAJEMEN KOMUNIKASI PT. PELNI SARANA BANDAR NASIONAL DALAM MEMBERIKAN PELAYANAN JASA LOGISTIK KEPADA PELANGGAN DI MAKASSAR - Indiatri Anwar , Astrid; Majid , Abdul; hadawiah, hadawiah (UNIVERSITAS MUSLIM INDONESIA, 2022)
The purpose of this research is to know the communication management process of PT. PELNI LOGISTISCS in providing logistics services and customer feedback regarding the services received. The type of research used is descriptive qualitative research with data collection techniques in the form of observation, documentation, and interviews. This research lasted for approximately 1 month and is located on Jl. General Sudirman No. 38 Makassar. The informants in this study were operational and administrative staff, general manager and terminal manager who used to serve customers and two of the customers of PT. PELNI LOGISTISCS which is able to provide information related to research. The results of the study, it can be concluded that the communication management process has 4 stages, namely, the first is careful planning, neat and good organization, the implementation goes according to a predetermined plan and the last is controlling or evaluating what has been done which is certainly supported by the staff. already experienced in their respective fields so that customers get comfort and satisfaction with the services they get and of course it will have an impact on the good image of the company.